“Turkistan collection” is an important resource in studying the history of the Russian Empire’s settlement policy of population to Turkistan (Scientific journal of the Fergana State University, 2023)
This article analyzes the source significance of the “Turkestan collection” in the study of the migration processes into the Turkestan region of Russian empire.